Relationship Between Scientific Literacy and the Ability to Solve Environmental Pollution Problems - Jariah, Yunita Ainun; Sigit, Diana Vivanti; Adisyahputra, Adisyahputra (FKIP Universitas Lampung, 2024)
Problem of environmental pollution is a challenge for all living things on earth. One effort that can be made to increase environmental awareness is through education. One of the agents who can be involved in overcoming various existing environmental problems is students. In order to support students' ability to solve environmental pollution, it is important to be able to involve their scientific literacy. This research is a quantitative descriptive study using a survey method conducted at 2 high schools in the Jakarta area, involving a total of 197 class XI Science students. The data used in this research includes the results of scientific literacy tests and tests of students' environmental pollution problem-solving abilities. Data testing in this research includes normality, homogeneity, and linearity for correlational and regression analysis. Based on the results of the research conducted, it can be concluded that there is a positive correlation between scientific literacy and students' ability to solve environmental pollution problems. Based on these results, the implication in this research is that students' problem-solving abilities can be improved through strong scientific literacy. Keywords: scientific literacy, problem-solving abilities, environmental pollution.DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1183-1198